Persistent symptomatic hyponatremia post-COVID 19: case report - Alshwikh, Haifa; Alshwikh, Ferial; Elshwekh, Halla (Journal of Clinical Nephrology, 2022)
Background: Hyponatremia associated with COVID-19 is considered an independent risk factor for a prolonged hospital stay, intensive care admission, and death, but its causes and treatment are not yet well known. Many workers attribute hyponatremia associated with COVID-19 to acute kidney injury and nephropathy associated with the disease. Others suggest that it is related to the syndrome of inappropriate antidiuretic hormone secretion, sepsis, or hypothalamic-pituitary dysfunction. We report a case of persistent acute hyponatremia in a COVID-19 patient with multifactorial etiology. Case presentation: A managed 77 years with known hypertension, type II DM, ischemic heart disease, chronic kidney disease (stage 3B and on treatment) presented with post-COVID-19 pneumonia, confusion, fever, generalized fatigability, dizziness, and lower limb edema. COVID-19 ad has been diagnosed two weeks earlier with a positive nasopharyngeal swab and was managed with dexamethasone, 10 mg oral for 10 days, azithromycin, 500 mg once orally, and levofloxacin, 500 mg once orally. At presentation, laboratory investigation showed hyponatremia (127.7 mg/dl). Conclusion: The etiology of hyponatremia associated with COVID-19 is different from that in other cases of hyponatremia and its management should be individualized according to patient history and clinical assessment, and effort is needed to determine the exact cause.